THE EFFECT OF DIFFERENT STOCKING DENSITIES ON THE GROWTH AND SURVIVAL OF BAUNG FISH (Mystus nemurus) ON THE MAINTENANCE MEDIA ADDED PROBIOTIC - Jonathan Erik Hutajulu; Niken Ayu Pamukas; Rusliadi Rusliadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                The aim of the study was to determine the best stocking density in the addition of probiotic for increasing the growth and survival rate of fish seed baung (Hemibagrus nemurus). This research was conducted for 40 days from May 11 to june 19 2019, in the Aquaculture Technology Laboratory of the Faculty of Fisheries and Marine University of Riau. This research was using the experimental method by completely random design (RAL) with 4 levels of treatment three replications. The treatments applied P1 = Maintenance with stocking densiy 200 tail/m3, P2 = Maintenance with stocking densiy 300 tail/m3, P3 = Maintenance with stocking densiy 400 tail/m3, P4 = Maintenance with stocking densiy 500 tail/m3. The results showed that the addition of different bioboost doses showed a significant effect (P <0,05) on absolute weight growth (Wm), absolute length growth (Lm), specific growth rate (LPS), feed conversion ratio (FCR) and no significant effect (P> 0,05) on survival rate (SR) of baung fish. The best treatment is stocking density 200 tail/m3 (P3) which produces absolute weight growth of 5,09 g, absolute length growth of 4,29 cm, the specific growth rate of 3,35 %, feed conversion ratio 1,42 and survival rate 95,27 % . Keywords: Stocking Density, Bacillus sp, Growth,  Mystus nemurus.